Evaluating an Emotional Awareness Intervention for Adolescents with Asperger Syndrome: Insights and outcomes - Relka, Georgia; Calmaestra Villén, Juan (IJERI: International Journal of Educational Research and Innovation, 2025)
The purpose of the study was to evaluate the effectiveness of intervention in improving emotional awareness in children with Asperger syndrome. The intervention guide of Alice Kassotaki (2015) for "Recognizing, Expressing & Regulating Emotions" was applied. The intervention is based on the methodology of the three levels of basic emotions. A survey was conducted in the age group of 12-15 years in North Greece. Emotional awareness scores of the experimental and control groups before and after intervention are compared. The results indicate that the intervention improved emotional awareness, which is crucial for social awareness and managing interpersonal relationships. This research suggests the importance of promoting further research in the field of social cognition and social emotions, which play a central role in socialization and social relations.